Development of transition mat scour protection design methodology and comparison to the state-of-the-practice - Turner, Michael D., author; Cox, Amanda L., author; Thornton, Christopher I., author; Colorado State University, publisher (Colorado State University. Libraries, 2011)
Culverts are designed to convey flow through or around obstructions such as roadway crossings, embankments, and riverine infrastructure. Flow exiting a culvert experiences an abrupt flow expansion generally resulting in flow regime changes and substantial energy dissipation. Such flow conditions can lead to bed scour, bank erosion, and local channel instability. Recent advancements in erosion control technology have resulted in the development of a class of products, termed transition mats (TM), designed to provide scour protection immediately downstream of culvert outlets. Colorado State University's Hydraulics Laboratory has conducted extensive testing of a transition mat under laboratory conditions to quantify system performance and develop a design methodology appropriate for implementing transition mats as scour protection. Prototype testing for both vegetated and unvegetated conditions has been coupled with Froude scale model data resulting in the development of an empirical method for determining an appropriate extent of culvert outfall protection and hydrodynamic design thresholds. Hydraulic conditions associated with flow in and around culverts have been well documented and the Federal Highway Administration has developed numerous tools designed to quantify flow conditions and implement scour mitigation designs. The purpose of this paper will be to quantify site hydraulics for three unique field conditions and then compare scour mitigation designs utilizing transition mats to accepted riprap design methodologies.
Hydrology days 2011
AGU hydrology days 2011
2011 annual AGU hydrology days was held at Colorado State University on March 21 - March 23, 2011.